ELECTRONIC BANKING TOOLS AND FINANCIAL PERFORMANCE OF COMMERCIAL BANKING IN RWANDA: A CASE STUDY OF BANK OF KIGALI - Shyaka, Patrick; Munene, Paul (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2021)
The purpose of this study was to analyze the contribution of e-banking tools on financial performance of commercial banks in Rwanda. Specifically, the study verified the contribution of ATMs use, mobile banking, and internet banking, and established the extent of contribution and link between those variables namely ATMs, mobile banking and internet banking on financial performance of Bank of Kigali. Descriptive survey design and correlational design were adopted. Fifty-two staff members from Bank of Kigali were the target population of Bank of Kigali. The information utilized in this research was quantitative in nature. Also, secondary information namely annual publications from 2016 to 2020 (5 years) were collected from Bank of Kigali. This included balance sheet, income statements and executives’ reports. Regression analysis was employed to examine the link between e-banking tools and performance of Bank of Kigali. To gather info, a form survey and interviews were adopted and SPSS 22 version supported in data analysis process. All ethical issues were considered. Through ought the data, it was concluded that many of participants agreed that ATMs contributed a lot on financial performance of BK; this was indicated by the overall mean of 4.612 and a Std.Dev of 0.4882. Majority also agreed that mobile banking contributed to financial performance of BK, evidenced by mean of 4.556 and Std.Dev. of 0.481. To the same extent the study also revealed that internet banking contributed to financial performance of BK, and this was evidenced by the overall mean of 4.610 and a standard deviation of 0.481. Looking at correlation, the study reported a positive degree of relationship between E-banking tools and financial performance at BK as indicated by the following ratios; 0.700, 1 and 0.422 for ATMs, mobile banking and internet banking respectively. Finally, the regression model of the study was Y: 4.321+0.667X1 + 0.308X2 + 0.213X3. In conclusion, these findings proved that e-banking tools contributed a lot to financial performance of Bank of Kigali, and in these recent years the use of e-banking tools in providing financial services have significantly increased meaning the revenues from the use of these tools also increased as shown by positive correlation within key variables under investigation. The researcher recommends Bank of Kigali and other financial institutions to put in place sustainable measures and infrastructures to maintain and improve the use of e-banking tools as they are great sources of income.